Cell Division Cycle 5-Like Regulates Metaphase-to-Anaphase Transition in Meiotic Oocyte - Zhang, Hong-Yong; Li, Jian; Ouyang, Ying-Chun; Meng, Tie-Gang; Zhang, Chun-Hui; Yue, Wei; Sun, Qing-Yuan; Qian, Wei-Ping (Frontiers in Cell and Developmental Biology, 2021)
The quality of oocyte is a vital factor for embryo development. Meiotic progression through metaphase I (MI) usually takes a relatively long time to ensure correct chromosome separation, a process that is critical for determining oocyte quality. Here we report that cell division cycle 5-like (Cdc5L) plays a critical role in regulating metaphase-to-anaphase I transition during mouse oocyte meiotic maturation. Knockdown of Cdc5L by siRNA injection did not affect spindle assembly but caused metaphase I arrest and subsequent reduced first polar body extrusion due to insufficient anaphase-promoting complex/cyclosome (APC/C) activity. We further showed that Cdc5L could also directly interact with securin, and Cdc5L knockdown led to a continuous high expression level of securin, causing severely compromised meiotic progression. The metaphase-to-anaphase I arrest caused by Cdc5L knockdown could be rescued by knockdown of endogenous securin. In summary, we reveal a novel role for Cdc5L in regulating mouse oocyte meiotic progression by interacting with securin.